Surface textures fabricated by laser and ultrasonic rolling for improving tribological properties of TiAlSiN coatings. (December 2021) - Meng, Ying; Deng, Jianxin; Ge, Dongliang; Wu, Jiaxing; Sun, Wei; Wang, Ran
Abstract: To enhance the tribological properties of the TiAlSiN coatings, two types of micro-textures were fabricated on the AISI 1045 steel substrates by laser texturing and ultrasonic rolling texturing prior to coating deposition. The mechanical properties and tribological behaviors of different samples were evaluated. Results revealed that the micro-textures improved the tribological properties of TiAlSiN coatings under dry friction and lubricant conditions. Under dry friction conditions, the friction coefficient and steel ball wear rate of the coatings decreased by 16.9% and 44.2%, respectively, after ultrasonic rolling texturing pretreatment, when compared with the coatings deposited on the polished substrates. Under lubricant conditions, the two values were reduced by 27.8% and 73.4%, respectively. The contribution of micro-textures was primarily to amplify lubrication, trap wear debris, decrease contact area and improve bearing capacity. The modification mechanism of the ultrasonic rolling texturing also benefited from the enhanced mechanical properties. Highlights: The mechanical property can be affected by surface texturing pretreatment. Laser and rolling texturing are effective in prolonging tribological properties. The improved anti-adhesive wear properties rely on the microtextures and hardness.